Bioindicator species for EROD activity measurements: A review with Australian fish as a case study - Gagnon, Marthe Monique; Rawson, C. (Elsevier, 2017)
The conversion of ethoxyresorufin to the fluorescent product resorufin by the enzyme ethoxyresorufin-O-deethylase (EROD) enables researchers to rapidly measure the upregulation of this protein in response to exposure to a range of organic contaminants e.g. PAH, PCBs. The EROD activity assay has been widely used to examine the effects of such pollutants on fish taxa in both laboratory and field studies. This review is intended to provide fundamental information for researchers using this EROD activity as an endpoint, including methods used in the assay, the species studied to date, the background EROD levels which would be expected for these species and when available, the EROD activity induction potential for these species. While the focus in on Australian studies, many species listed in this review have a worldwide distribution and the information presented may be extend to other bioindicator fish species. Common shortfalls in the published literature leads to recommendations: it is recommended to have multiple laboratory control or field reference groups as basal EROD activity might vary with biotic and/or abiotic factors. The use of native species over introduced species offers no advantages, with EROD activity induction potential (x-fold) being similar for native or introduced fish species. Similarly, in laboratory studies, EROD activity induction potential is comparable for lab/hatchery-reared fish to the activity observed in field-caught animals. Because EROD activity is often reported to reduce at high concentrations of toxicants, laboratory studies should use a carefully considered range of contaminant concentrations rather than a single exposure concentration, as a single exposure concentration may be on the decreasing side of the response curve. The measurement of serum sorbitol dehydrogenase (SDH) activity in conjunction with EROD activity is recommended to insure liver functions are not jeopardized by high contaminant levels. In field studies, and depending on the variability observed in EROD activity within a given fish species, a number of 8–13 non-reproductively active fish, preferably of similar age and sex, per site is recommended to improve the chances of detecting a significant difference in EROD activity, if one does exist. Finally, an inter-continental comparison of EROD activity induction potential (expressed as x-fold relative to a control or reference group) suggests that highly inducible species can be found on all continents, with reported EROD activity induction as high as 135-fold in exposed groups but more commonly less than 5-fold relative to laboratory control or field reference groups.